The effect of exclusive breastfeeding on reducing acute respiratory infections in low birth weight infants - Karolina Trigemayanti Tallo; I Kompyang Gede Suandi; Setya Wandita (Indonesian Pediatric Society Publishing House, 2012)
Background Infants who are breastfed receive natural protection against certain infections. Despite the known benefits of exclusive breastfeeding, many Indonesian mothers choose to supplement with formula. There have been few Indonesian studies on the effect of exclusive breastfeeding in reducing acute respiratory infections in low birth weight infants in their first four months of life. Objective To investigate the effect of exclusive breastfeeding in reducing the incidence of acute respiratory infections in low birth weight infants during their first four months of life. Methods We conducted a prospective cohort study on low birth weight babies in Sanglah Hospital, Denpasar. The total number of subjects was 181. The incidence of acute respiratory infections during the first 4 months of life and the duration of breast feeding were assessed by questionnaires. Data was analyzed Mth Chi square and logistic regression tests. Results Infants who were exclusively breastfed for 4 months had a lower risk of acute respiratory infection than those who were not exclusively breastfed (RR 0.07; 95% CI 0.03 to 0.14; P􀁄O.OOI). After adjustment for gestational age, parity, maternal nutritional status, family size, smoke exposure, and history of atopy, infants who were exclusively breastfed still had a lower risk for acute respiratory infection than those who were not exclusively breastfed (RR 0.06; 95% CI 0.03 to 0.13; P 􀁄 0.001) Conclusion Exclusive breastfeeding reduced the risk of acute respiratory infection in low birth weight infants in the first four months after birth. [Paediatr Indones. 2012;52:229,32].